Atrazine biodegradation efficiency, metabolite detection, and trzD gene expression by enrichment bacterial cultures from agricultural soil - Solomon, Robinson David Jebakumar; Kumar, Amit; Satheeja Santhi, Velayudhan (Journal of Zhejiang University. B. Science, 2013)
Atrazine is a selective herbicide used in agricultural fields to control the emergence of broadleaf and grassy weeds. The persistence of this herbicide is influenced by the metabolic action of habituated native microor-ganisms. This study provides information on the occurrence of atrazine mineralizing bacterial strains with faster me-tabolizing ability. The enrichment cultures were tested for the biodegradation of atrazine by high-performance liquid chromatography （HPLC） and mass spectrometry. Nine cultures JS01.Deg01 to JS09.Deg01 were identified as the degrader of atrazine in the enrichment culture. The three isolates JS04.Deg01, JS07.Deg01, and JS08.Deg01 were identified as efficient atrazine metabolizers. Isolates JS04.Deg01 and JS07.Deg01 produced hydroxyatrazine （HA） N-isopropylammelide and cyanuric acid by dealkylation reaction. The isolate JS08.Deg01 generated deethylatrazine （DEA）, deisopropylatrazine （DIA）, and cyanuric acid by N-dealkylation in the upper degradation pathway and later it incorporated cyanuric acid in their biomass by the lower degradation pathway. The optimum pH for degrading atrazine by JS08.Deg01 was 7.0 and 16S rDNA phylogenetic typing identified it as Enterobacter cloacae strain JS08.Deg01. The highest atrazine mineralization was observed in case of isolate JS08.Deg01, where an ample amount of trzD mRNA was quantified at 72 h of incubation with atrazine. Atrazine bioremediating isolate E. cloacae strain JS08.Deg01 could be the better environmental remediator of agricultural soils and the crop fields contaminated with atrazine could be the source of the efficient biodegrading microbial strains for the environmental cleanup process.